Preparation and characterization of novel VAc/VeoVa10/DBM/VTES quadripolymer latex emulsified with green surfactants. Issue 4 (November 2019) - Chen, Lijun; Shao, Tantan; Gong, Yilu; Wang, Xiuming
The novel vinyl acetate (VAc)/vinyl neo-decanoate (VeoVa10)/dibutyl maleate/triethoxy vinyl silane quadripolymer latex was prepared via the semi-continuous seeded emulsion polymerization emulsified with disodium laureth sulfosuccinate (AEMES) as anionic surfactant and beta-cyclodextrin (β-CD) mixture as emulsifier and initiated with potassium persulfate (KPS), respectively. The chemical compositions of copolymer was determined by Fourier transform infrared spectromer (FTIR). The glass transition temperature ( T g ) of the copolymer was measured by differential scanning calorimetry. The water resistance of the film was assessed by the water contact angle measurement. The conditions of preparing the novel latex were optimized and obtained as follows. The amount of AEMES and β-CD mixtures were 6 wt% and the mass ratio of AEMES to β-CD were 1:1. The dosage of KPS was 0.6 wt% and the mass ratio of VAc to VeoVa10 was 3:1. The amount of dibutyl maleate and triethoxy vinyl silane was 4% and 3%, respectively. In this case, the conversion percentage of the mixed monomers was 99.0% and the polymerization stability was good.